Rome and her Empire - Shotter, D. C. A. (David Colin Arthur) (Recovering the past., 2014)
The name of Rome excites a picture of power and organisation, as do the widely-spread ruins that Roman civilization left behind. Yet Rome grew out of a collection of small villages and major developments such as the growth of Empire were unplanned and completely unprepared for. Influenced by a small number of self-interested aristocrats who lacked a broader vision, Rome was often threatened by their intrigues. Brought to the ground on a number of occasions, its leaders were able to snatch victory from the jaws of defeat. How did Rome survive for nearly 1000 years, ruling over millions of people.